Strategi Pengembangan Program Pembelajaran Pendidikan Agama Islam Sekolah: The Development Strategy of Islamic Religious Education Learning Programs - Diana Susilawati Sj; Muhammad Anas Maarif; Afif Zamroni (Tafkir: Interdisciplinary Journal of Islamic Education, 2021)
The research objective is to describe the process of planning, implementing and controlling the development of Islamic religious education learning programs. The type of research used is qualitative with a case study approach. Data collection techniques using interviews, observation and documentation. informants who are the source of information are the principal, vice principal, curriculum assistant, religion teacher and extracurricular coaches. The results of the research are: 1) planning for the development of Islamic religious education learning programs can be seen in the form of learning tools or programs which include syllabus development, annual plans, semester programs and teaching preparation in the form of learning implementation plans which are based on a study of competency standards, basic competencies and indicators. which is determined based on content standards, competency standards for graduates of Islamic religious education subjects. 2) Implementation of developing learning programs, namely carrying out learning program development activities, following the applicable procedures in schools, namely by organizing and directing the development of learning programs with reference to intracurricular and extracurricular learning. This study also found that controlling the implementation of the learning program was carried out by evaluating student learning outcomes and monitoring class in intracurricular and extracurricular learning.